Stolen from the Snows: John Kinsella as Poet and as Fiction Writer. Issue 2 (August 2020) - Birns, Nicholas
Abstract : This piece explores the fiction of John Kinsella, describing how it both complements and differs from his poetry, and how it speaks to the various aspect of his literary and artistic identity, After delineating several characteristic traits of Kinsella's fictional oeuvre, and providing a close reading of one of Kinsella's Graphology poems to give a sense of his current lyrical praxis, the balance of the essay is devoted to a close analysis of Hotel Impossible, the Kinsella novella included in this issue of CounterText . In Hotel Impossible Kinsella examines the assets and liabilities of cosmopolitanism through the metaphor of the all-inclusive hotel that envelops humanity in its breadth but also constrains through its repressive, generalising conformity. Through the peregrinations of the anti-protagonist Pilgrim, as he works out his relationships with Sister and the Watchmaker, we see how relationships interact with contemporary institutions of power. In a style at once challenging and accessible, Kinsella presents a fractured mirror of our own reality.